Responsabilidad social y su relación con la satisfacción laboral de los colaboradores del hospital de emergencia de EsSalud, Iquitos 2023 - Luna Garcia, Veronica Pilar (2023)
The objective of this thesis is to determine the relationship between social responsibility and job satisfaction of the users-collaborators of the Essalud emergency hospital, Iquitos 2023. The research is of a descriptive correlational type, with a quantitative approach where it is intended to expose the development of the facts occurred from rigorous procedures. With the results obtained from the existence of a relationship between social responsibility and job satisfaction of the users-collaborators of the Essalud emergency hospital, Iquitos 2023.